Length heterogeneity of a conserved displacement-loop sequence in human mitochondrial DNA. - Hauswirth, W W (1985)
Mitochondrial DNA from human tissue culture cells contains heterogeneous sequences located within a previously identified, evolutionarily conserved region termed CSB-2. CSB-2 is located near the origin of heavy-strand mitochondrial DNA synthesis and the major transcriptional promoters for each strand of human mitochondrial DNA. Nucleotide sequence analysis of cloned mitochondrial DNA and electrophoretic analysis of appropriate small fragments from cellular mitochondrial DNA show that the variability is limited to a homopolymer sequence which can range in length from 6 to 12 residues. In vitro transcriptional analyses, using several of these cloned length polymorphs as templates and partially purified human mitochondrial RNA polymerase, demonstrate that the most common polymorphs will support accurate transcriptional initiation.